Strategy For Youth Interest Enhancement as Effort of Agriculture Revitalizational in Klaten Regency - Sri Eka Wulandari; Sucihatiningsih Dian Wisika Prajanti (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2018)
The aims of this study were to examine the condition and obstacles and to arrange priority of strategy for youth interest enhancement as effort of agriculture revitalization in Klaten Regency. Method used in this study was qualitative descriptive method with Analysis Hierarchy Process (AHP). The number of interviewees in this research was 11 key person. From the result of this study showed that institutional criteria was the most priority aspect, followed by human resources criteria, and the last was government policy criteria. Alternative program which has been prioritized is formation of youth farmers' groups, socialization facilities and human resources of agricultural instructors which are not being converted and transferred, and self-help and private instructor should be optimized. Based on those priorities, it is suggested that the local government of Klaten District through Department of Agriculture can optimize and control the implementation of those programs. Besides, it is needed the participation of various parties such as academia, farmer institution, farmer entrepreneur, youth and related government institution in order to increase youth interest as effort of agriculture revitalization in Klaten Regency can run well and continuously.